Return to face-to-face academic activities and incidence of Covid-19 in a medical course during the pandemic period (Research, Society and Development, 2022)
The objectives of this article are to know the incidence of COVID-19 among medical students, and the vaccination status, compare and statistically analyze the different periods regarding the variables incidence and practical activity in a health unit and analyze adherence to control measures. An observational, retrospective, cross-sectional, individual study was carried out, covering the period from April/2020 to February/2022, including students from the first to the twelfth period of Medicine at a university in the Baixada Fluminense region, Rio de Janeiro. Data collection through an online questionnaire, as approved by the Research Ethics Committee - CEP. Analysis of absolute and relative frequencies. Data treatment by Chi-Square (χ2) test for qualitative variables. A sample of 173 individuals was obtained, of which 109(63%) were affected, 46(42.2%) were aged 17 to 26, and females. Peaks in the frequency of cases were verified in non-school periods or during remote teaching, following the municipal and national scenarios. Only 3.46% were not vaccinated, and 38.15% reported an incomplete vaccination schedule. A lower chance of the disease was observed in students in periods with practical activities in Health Units (HU) (OR =0.387; χ2 =8.824; p=0.003). With these results, it was possible to suggest that, despite the methodological limitations, academic life was not associated with an increase in the chance of acquiring the disease and may contribute to the decision regarding the maintenance of face-to-face teaching safely in the pandemic context, reinforcing the importance of control measures in the university environment, especially vaccination and the use of masks.